2022
DOI: 10.1002/app.52126
|View full text |Cite
|
Sign up to set email alerts
|

Influence of co‐neutralization by sodium and zinc on the ethylene ionomer structure and properties

Abstract: This study investigates the properties and structure of poly(ethylene‐co‐methacrylic acid) (EMAA) ionomers co‐neutralized by zinc and sodium, and compares them with ionomers neutralized by a single metal: zinc (EMAA‐Zn) and sodium (EMAA‐Na). The bending stiffness and the degree of crystallization for the co‐neutralized ionomer (Na:Zn = ~1:1 on a molar basis) gives 16.5% and 9.8% increase compared to the simple average of their single cation counterparts. Such unusual properties are seen in mechanical, thermal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…In our case, a better fit is achieved with a band at 1565 cm −1 . The band existing at 1585 cm −1 is assigned to a 4-coordination (COO − ) configuration around the cation [66]. This band is dominant in Zn 2+ neutralized ionomers because of its strong and well-designed complexion with (COO − ) groups.…”
Section: Structural Features Of Blends By Ftir Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, a better fit is achieved with a band at 1565 cm −1 . The band existing at 1585 cm −1 is assigned to a 4-coordination (COO − ) configuration around the cation [66]. This band is dominant in Zn 2+ neutralized ionomers because of its strong and well-designed complexion with (COO − ) groups.…”
Section: Structural Features Of Blends By Ftir Analysismentioning
confidence: 99%
“…Water, temperature, pressure and neutralization percentage have been shown to change the fingerprint spectrum in this region [67,[71][72][73]. Simultaneous neutralization by more than one cation also modifies the spectrum [66,74,75]. It was concluded that this is due to local disturbance of the configurations of the coordination complexes.…”
Section: Structural Features Of Blends By Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation